A new indication for elective induction of labor COVID-19 pandemic effect - Nandal, Isha; Kochar, Surinder Pal Singh; Kaur, Rajvir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Induction of labour is performed in certain circumstances which involve greater risks of waiting for the onset of spontaneous labour than the risks due to shortening the duration of pregnancy by induction. The objective of this study was to evaluate the maternal and fetal outcome in patients undergoing elective induction during COVID-19 pandemic. Methods: This prospective observational study was conducted on 60 ANC patients with singleton pregnancy and POG >39 weeks coming to OPD with negative COVID-19 RT-PCR report. To avoid the burden of repeat testing after one week and risk of exposure to COVID-19 virus from community, patients were induced. All the data was recorded and analyzed. Results: Most of the patients were in age group of 20-25 years (50%) and only 6.7% of the patients were older than 30 years. 32 (53.3%) patients were multiparous and 50% of the patients were having Bishop score between 2-5 and only 8.3% had bishop score of more than 5. 47 patients (78.3%) underwent normal vagina delivery whereas 12 patients (20%) underwent LSCS. Failure of Induction was the indication for LSCS in 5 patients (41.7%). Conclusions: Elective induction was found to be better option in COVID-19 negative patients. All pregnant women should be monitored for development of symptoms and signs of COVID-19 particularly if they have had close contact with a confirmed case. Pregnancy and childbirth generally do not increase the risk for acquiring SARS-CoV-2 infection but may worsen the clinical course of COVID-19 compared with nonpregnant individuals of the same age.